Global Crises and Contagion: Does the Capitalization Size Matter? - Kenourgios, D.; D. Dimitriou; A. Samitas (Applied Economics Quarterly, 2018)
This paper investigates the spread of the Global Financial Crisis (GFC) and the Eurozone Sovereign Debt Crisis (ESDC) to different market capitalization segments across countries and regions. Specifically, it tests for capitalization-specific contagion across both crises and their phases by examining large, medium and small capitalization indices of G-20 equity markets. The analysis across stable and the two crisis periods shows the existence of a stronger largecap transmission channel for the majority of countries. On the other hand, the contagion dynamics across the phases of the two crises do not provide a clear pattern of a specific cap size-based contagion across all markets. However, there is evidence that the Pacific region and the three cap groups of some individual markets of different regions are less severely affected. Further, all three cap groups of developed markets are mostly affected during the last phase of the ESDC, while emerging and frontier markets show a more diverse pattern of contagion across the phases of both crises. Finally, the Lehman Brothers’ collapse triggers a dramatic increase of the infection rate, while the ESDC seems to be more contagious than the GFC.